The Role of Pay, Job Security and Sales Force Motivation in Supply Chain Performance: A Case of Indonesian Distribution Companies - Nandang Najmulmunir (International Journal of Supply Chain Management, 2020)
Objective of this study is to examine the role of employee pay, job security and sales force motivation to expediate supply chain performance (SCP). For this purpose, Indonesian distribution companies were selected, and employees of these companies were preferred as the respondents of the study. Questionnaires were distributed among the employees of distribution companies with the help of cluster sampling. Five hypotheses were developed in this study with the help of previous studies. Structural Equation Modeling (SEM) was used to test the hypotheses. It is found that employee’s pay and higher job security are the most important factors which has significant contribution to the motivation of sales force. Results of the study highlighted that employee pay, job security and sales force motivation have positive effect on SCP. Better the employee’s pay and higher job security lead to the sales force motivation which shows positive effect on SCP. Therefore, Indonesian distribution companies should focus on employee pay, job security and sales force motivation to enhance SCP.